1993
DOI: 10.1109/77.233787
|View full text |Cite
|
Sign up to set email alerts
|

Quench characteristics of 5-cm-aperture, 15-m-long SSC dipole magnet prototypes

Abstract: The quench performance and ramp rate sensitivity of eighteen 5-cm-aperture, 15-m-long SSC dipole magnet prototypes are discussed. All the magnets appear to reach a quench plateau near their extrapolated short sample current limit and well in excess of the operating current with very little training. Most of the magnets, however, exhibit a dramatic degradation of their quench current as a function of ramp rate, which for the most part, can be attributed to large cable eddy currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…2(a) of [2] can be explained in the following way using results of combinations A and B: though the current distribution is nonuniform due to the existence of "supercurrents", the MQE did not drop to very low lever. Therefore, magnets' quench currents decrease with the increase of ramp rate mainly due to the increase of AC losses.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…2(a) of [2] can be explained in the following way using results of combinations A and B: though the current distribution is nonuniform due to the existence of "supercurrents", the MQE did not drop to very low lever. Therefore, magnets' quench currents decrease with the increase of ramp rate mainly due to the increase of AC losses.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 94%
“…It is reported that for a low ramp rate (e.g., 1 A/s), quench of SSC dipole magnet prototypes generally originated at the coil end, whereas for a high ramp rate, quench origin moves to the middle plane of coil inner layer [2]. On the middle plane of coil inner layer, the magnetic field is more perpendicular to the wider face of Rutherford cable.…”
Section: A Current Non-uniformity Ratio In Accelerator Magnetsmentioning
confidence: 98%
See 3 more Smart Citations